Doomscrolling Spirituality On The Morality Of Islamic Students In Surabaya - Muhammad Munir; Moh. Taufiq (Da'wa Faculty of Islamic State University Salatiga, 2024)
The impact of social media extends beyond individual experiences to profoundly influence global societal structures, economic systems, and cultural paradigms. Within the specific context of Muslim university students in Surabaya, Indonesia, social media engagement intersects uniquely with religious practice and social identity formation. The emergence of social media has fundamentally altered contemporary communication patterns, particularly through the phenomenon of